Business ethics: Should the punishment fit the crime? - Leyland F. Pitt; Richard T. Watson; Deon Nel (South African Journal of Business Management, 1990)
In this paper an empirical investigation is reported of the attitudes of purchasing managers to the degree of wrongness of a range of ethically problematical Issues and what the corresponding punishment should be for these actions. The study found a significant difference between what purchasing managers believe is wrong and how willing they are to punish transgressors. It is suggested that the largest difference between a wrongful action and its punishment occurs when the action is clearly wrong, but the financial impact upon the employer is minor. The paper concludes by suggesting areas for future research that could explore why there is a difference between a crime and its associated punishment.
Keywords: 650